If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 5 = 3x + -8 Reorder the terms: 5 + y = 3x + -8 Reorder the terms: 5 + y = -8 + 3x Solving 5 + y = -8 + 3x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + y = -8 + -5 + 3x Combine like terms: 5 + -5 = 0 0 + y = -8 + -5 + 3x y = -8 + -5 + 3x Combine like terms: -8 + -5 = -13 y = -13 + 3x Simplifying y = -13 + 3x
| 8x+4(x-1)=20 | | X+(x-15)=44 | | 5(x+5y)-3(x-2y)= | | x^2+21x-20=0 | | 20+15=50-x | | 6-4a=a+6 | | x-8y=58 | | k/10=8/4 | | (12x-34)=180 | | 2x+x+3y=180 | | y/3-9=12 | | megan+G= | | 8x+50=12x-174 | | MEGA= | | X+5X=165 | | y=1.5*-1+6 | | 7=7x+3(5x-13) | | 6(x-2)=8x-12-2x | | y=1.5*1+6 | | 23.5+y=68.88 | | 2x+13=2(x+5) | | 64+6x=208 | | 8=12+p | | 3=-9+z | | c^2+3x+2=0 | | y=1.5*0+6 | | x-9y=65 | | y=2x+0.4 | | (38.5)(12.5)= | | 3x+y=69 | | t=c-x/x | | y+1+(-1)-(-2)=y+3-1-(-y) |